A comparative study of tensile properties of eutectic Al-Si / ZrO2 composites fabricated by spray forming and stir casting methods. Issue 3 (3rd July 2022) - Goudar, Dayanand M.; Patil, Ishwargouda S; Magalad, Veeresh T.; Rao, Shrikantha S; Herbert, Mervin A
ABSTRACT: The study aims to investigate the microstructural and mechanical properties of Al-12.5%Si matrix composites reinforced with ZrO2 were fabricated by spray forming method and stir casting (SC) technique by varying reinforcement of 2%, 6% and 10 wt.% ZrO2 powder (size 25 μm).The spray-formed (SD) composites were subjected to hot (400°C) isostatic pressing to reduce the porosity. The microstructure of spray-formed and SC composites were examined using optical and SEM/ EDS. The microstructure of the spray-formed composites showed uniform distribution of fine Si, eutectic phase and ZrO2 particles in the equiaxed Al-matrix. In contrast, SC composites consist of a coarse Si, needle like eutectic phase and clustering of reinforcement particles at grain junctions as a continuous network along the grain boundaries. The hardness, ultimate tensile strength of both spray-formed and SC composites improved as the ZrO2 content increased, while yield strength decreased. Spray-formed composites showed better mechanical properties. This was attributed to uniform distribution fine of Si particles, reinforced particles, equiaxed matrix induced during spray deposition process. Tensile fracture surface of spray-formed composites possess ductile and cleavage fractures. SC composites showed intragranular cracks in coarse Si particles and increase in micro-cracks with increasing reinforcement.